Medium- to long-term functional outcomes of artcure diffusional patch therapy for lumbar disc herniation: which herniation is more likely to require surgery? - Zekeriya Ersin Çelen; Furkan Hanege; Soner Sarı; Bülent Özkurt (BMC Musculoskeletal Disorders)
Abstract Background Artcure diffusional patch (ADP) is a novel transdermal therapeutic system that started to be used in the last decade for lumbar disc herniation (LDH). Previous studies have reported early results of the therapy. In this study, we aimed to evaluate the medium- to long-term functional outcomes of this treatment in LDH patients and examine factors predicting the need for surgery after treatment. Methods Totally, 270 patients with single-level LDH were included. ADP was applied transdermally to the lumbar regions of the patients. Outcomes measures included the Oswestry Disability Index (ODI) and leg and low back visual analog scales (VAS). Herniations were graded using the Michigan State University (MSU) classification. The predictive factors for surgery need were analyzed with logistic regression analysis. Results The average follow-up duration was 43.8 ± 4.8 months. The average VAS and ODI scores of the patients decreased significantly at the first month and final visits compared to admission values (p < 0.001). Within the follow-up period, 19 (7.0%) patients underwent surgery. The results of the multivariate analysis showed that ≥ 2 MSU grade of the herniation was a significant predictive factor for operation need (HR: 7.32 (1.87–28.57), p = 0.004). Conclusion Single-dose ADP therapy is a safe and feasible treatment option in the treatment of single-level LDH and can achieve favorable functional and pain scores at medium- to long-term. Patients with MSU grade two and three herniations should be monitored more closely, as they are more likely to experience a later surgical intervention. Clinical trial number Not applicable.